Complicity and Cambridge poetry. Issue 4 (7th June 2017) - Ramesh Sankar, Nandini
ABSTRACT: This paper studies the concept of complicity through the work of two Cambridge School poets, J.H. Prynne and Peter Riley. The acknowledgement of complicity in social, political, and economic injustices has been central for poets influenced by J.H. Prynne, and the resulting poetry, often difficult and alienating, nevertheless seeks to give lyric expression to the historical burden of being at the dispensing end of global violence. Peter Riley's work, on the other hand, implies an ethical position that also includes a real possibility of opting out of exploitative and violent historical tendencies: complicity here is emphatically within the ambit of volition. Through readings of Prynne's 'Refuse Collection' – which was written in response to the torture at Abu Ghraib – and Riley's Alstonefield: A Poem and Excavations, this paper argues that the differences between these positions are more a matter of emphasis than of kind.